1984
DOI: 10.1159/000183238
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Immune Complex Nephritis in Streptozotocin-Induced Diabetic Rats

Abstract: In order to investigate the influence of diabetes mellitus on immune complex-mediated nephritis, we produced Heymann nephritis in streptozotocin-induced diabetic rats (DM-HN group) in which the clinical course for 24 weeks and histological changes were examined. Nondiabetic rats with Heymann nephritis (HN group) and diabetic rats (DM group) were also examined as controls. The degree of proteinuria, hypoproteinemia, hyperlipidemia and anemia were more pronounced and the mortality rate was higher in the DM-HN gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Rao and Cresson [19] suggest that the complica tion of MGN in patients with diabetic glomerulosclerosis may aggrevate renal dysfunction requiring early dialysis or renal transplant. Okuda et al [17] reported that the mortality rate of the rats with Heymann nephritis compli cating streptozotocin-induced diabetes was higher than those with no complication. There are, however, no large series studies concerning the effects of the coexistence of superimposed GN on long-term prognosis in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rao and Cresson [19] suggest that the complica tion of MGN in patients with diabetic glomerulosclerosis may aggrevate renal dysfunction requiring early dialysis or renal transplant. Okuda et al [17] reported that the mortality rate of the rats with Heymann nephritis compli cating streptozotocin-induced diabetes was higher than those with no complication. There are, however, no large series studies concerning the effects of the coexistence of superimposed GN on long-term prognosis in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Larger and more numerous immune complexes were seen in diabetic rats upon induction of Heymann nephritis than their nondiabetic counterparts. [21] Our patients with DPGN on a background of DN showed significantly worse outcomes compared to their nondiabetic counterparts; 85% required dialysis and the renal function did not return to baseline in any case. This was in sharp contrast to the nondiabetic adults with PIGN, who showed complete and partial recovery in 45% and 36% of cases respectively.…”
Section: Discussionmentioning
confidence: 68%
“…First, electron microscopy showed that the amount of the subendothelial electron-dense deposits was greater in the PM-UN group than in the UN group. Okuda et al (1984) and Abrass and Cohen (1987) reported that diabetic rats with Heymann nephritis developed more intensely stained immune deposits along the capillary wall and mesangium than control rats with Heymann nephritis. Okuda et al explained this phenomenon by the contributions of three suggested mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments with rats, Okuda et al (1984) and Abrass and Cohen (1987) have found that the renal lesions produced by immunological insult of the glomeruli in diabetic rats were more severe than those produced in nondiabetic rats. They induced Heymann nephritis as a model of idiopathic membranous glomerulonephritis in streptozotocin-induced diabetic rats.…”
mentioning
confidence: 99%